A High-Speed Fully-Integrated VLC Receiver With Large-Area Photodetector - Sheng Xie; Xiaoxia Hu; Jia Cong (IEEE Photonics Journal)
This paper presents a fully integrated visible light communication (VLC) receiver with a large photo-sensitive area optimized for high-speed data transmission. The photodetector (PD) featuring a size of 410 μm × 410 μm is implemented using a P $^{+}$ /N-well/P-sub structure and was segmented into multiple P $^{+}$ /N-well detection cells to enhance the response speed while maintaining high sensitivity. To further extend the overall bandwidth of optical receiver, a continuous-time linear equalizer (CTLE) with negative capacitance technique is incorporated, effectively compensating for the high-frequency gain loss. The proposed VLC receiver was fabricated in CSMC 0.25 μm CMOS technology, and its performance is verified in a VLC test system. The experimental results indicate that this receiver can achieve a data rate of 980 Mbit/s at a bit error rate (BER) of 3.8 × 10 $^{-3}$ .